PEMBATASAN KEBEBASAN BEREKSPRESI DALAM DEMONSTRASI 2025 DI INDONESIA DITINJAU DARI PRINSIP RULE OF LAW - Rudi Santoso; Erry Meta; Fikri Hadi (Fakultas Ilmu Sosial dan Humaniora, 2026)
Freedom of expression and speech is a constitutional right guaranteed in Article 28E Paragraphs (2) and (3) of the 1945 Constitution, and is included as a right that cannot be reduced under any circumstances according to Article 28I Paragraph (1). However, in the context of demonstrations, problems sometimes arise in the form of riots and looting, as occurred during the demonstrations in August-September 2025 in Indonesia. This normative study aims to analyze the restrictions on freedom of expression in the 2025 demonstrations in Indonesia from the perspective of the principle of the rule of law. Using a statute and conceptual approach, this study examines the legal regulations governing these constitutional rights and the government's application of the principle of the rule of law. The results show that restrictions on freedom of expression are regulated in a limited manner in Article 28J Paragraph (2) of the 1945 Constitution and Law Number 9 of 1998. In the context of the 2025 demonstrations, which were marred by violence and looting, if the government wishes to impose restrictions, their application must refer to principle of the rule of law, which encompasses three main pillars: the supremacy of law (legal certainty and restrictions on the power of officials), equality before the law (equal treatment and accountability of officials), and the principle of proportionality. Any restrictions imposed by the state must have a valid legal basis, be aimed at protecting legitimate objectives and proportionate in a democratic society, in accordance with international human rights law standards.